Novel Imaging Approaches for Predicting Arrhythmic Risk. (November 2015) - Travin, Mark I.; Feng, DaLi; Taub, Cynthia C.
Abstract : Determination of ventricular arrhythmic risk is crucial for guiding management of cardiac disease. Although for patients at increased risk an implantable cardioverter-defibrillator is recommended, it is widely acknowledged that current criteria for device use based predominantly on left ventricular ejection fraction are deficient. Genesis of ventricular arrhythmias involves a complex interaction of myocardial substrate abnormalities, precipitating triggers, and modulating factors. There are much data showing that by more directly assessing these factors, noninvasive imaging using echocardiography, radionuclide imaging, and cardiac magnetic resonance enhances arrhythmic risk stratification beyond ejection fraction and commonly used electrocardiographic and serum biomarkers. It is anticipated that further technological advancements studied in well-designed clinical trials will provide both more precise determination of risk and guide therapies to enhanced survival and patient well-being.